Kan det finnes kime til livsmot i forskningssamtaler med etterlatte pårørende, der sorg danner bakteppe? - Lind, Ranveig (Nordisk tidsskrift for helseforskning, 2019)
Can research conversations with the relatives of deceased ICU patients provide the germ of courage for life against a backdrop of grief?This essay deals with conducting research interviews with the relatives of deceased ICU patients, where grief is a fundamental element. Based on the underlying profound seriousness of these conversations, the term “interview” is discarded in order to emphasize their relational aspect. Care and consideration to maintain dignity is shaped by these research conversations. The relationship between researcher and participant is not of a private nature. Yet a dialogue that persistently aims at the research goal is not possible either. The text touches on the various considerations necessary to include when planning and conducting studies aimed at this group of relatives. The risk of role change from researcher to therapist is described. But the ethical care aspect of this interpersonal encounter is of greater importance than the “therapeutic” aspect. Against the backdrop of a life phenomenon such as grief, care is used to protect the other and promote courage for life. The material is drawn from reflections on research interviews for a PhD project that was completed in 2013.
Keywords: research interviews; considerations; bereaved; death; critical care patients; forskningsintervjuer; overveielser; etterlatte; død; intensivpasienter